Changing Quaternary Environment in the Mediterranean - Maša Surić; Lara Wacha (Geosciences, 2022)
Reconstruction of the Quaternary environment is one of the main issues in the global endeavour of predicting future changes, to which the Mediterranean Sea is highly sensitive due to its latitude and landlocked position [...]